Translations of Verses of Ghalib: Analysis, Comparison and Notes - Muhammad Qasim (بازیافت, 2022)
THE URDU CLASSICAL POETRY ABOUNDS IN NUMEROUS NOTABLE ARTISTIC EXERTIONS .HOWEVER, MUCH A LESS ENDEAVORS HAVE BEEN DONE TO MAKE THESE CIVILIZATIONAL ASSETS ACCESSIBLE IN INTERNATIONAL LINGUAL MEDIUMS .MIRZA ASADULLAH KHAN GHALIB IS THE ONLY POET WHOSE INMOST THOUGHTS AND IDEAS HAVE REACHED IN WESTERN LITERARY CIRCLES THROUGH A NUMBER OF TRANSLATIONS .ALTHOUGH THESE TRANSLATIONS OF GHALIB APPEARED TO BE DEVOID OF HIS TRUE ESSENCE, HOWEVER INCREASING TENDENCY OF TRANSLATING GHALIBS POETRY IN EAST AND WEST, BEYOND THE BOUNDARIES ,TIME AND PLACE, IS THE TESTIMONY TO THE FACT THAT STRIVINGS OF TRANSLATORS AND COMMENTATORS HAVE NOT GONE IN VAIN. THIS ARTICLE IS THE FIRST UNIQUE, INTEGRATED AND ANALYTIC STUDY IN TERMS OF COMPARISON OF 28 TRANSLATIONS AND ANNOTATIONS ABOUT INTERPRETATORS.IN THE GALAXY OF THESE TRANSLATORS WE CAN SEE POETS, WRITERS, CRITICS, ORIENTALISTS, JOURNALISTS, SCIENTISTS ETC, PEOPLE FROM ALL WALK OF LIFE FROM PAKISTAN, INDIA, USA ,UK .TODAY THEIR WORK IS  AVAILABLE TO US BUT THESE TRANSLATORS HAVE BEEN LOST IN THE DUST OF TIME. THE ARTICLE UNDER REVIEW ATTEMPTS TO SEARCH OUT AND COMPILE THE PROFILE OF THESE TRANSLATORS.